Dissecting the Genetic Basis of Lateral and Central Spikelet Development and Grain Traits in Intermedium-Spike Barley (Hordeum vulgare Convar. Intermedium) - Youssef, Helmy M. (Plants (Basel), 2020)
Barley (Hordeum vulgare L.) is one of the major grain crops worldwide and considered as a model plant for temperate cereals. One of the barley row-type groups, named intermedium-barley, was used in our previous study where we reported that other genetic loci rather than vrs1 and Int-c could play a role in lateral spikelet development and even in setting grains. To continue this work, we used phenotypic and genotypic data of 254 intermedium-spike barley accessions aimed at dissecting the genetic basis of development and grain traits of lateral and central spikelet using genome wide association (GWAS) analysis. After genotypic data filtering, 8,653 single-nucleotide polymorphism (SNPs) were used for GWAS analysis. A total of 169 significant associations were identified and we focused only on the subset of associations that exceeded the p < 10(−4) threshold. Thirty-three highly significant marker-trait-associations (MTAs), represented in 28 different SNPs on all seven chromosomes for the central and/or lateral spikelet traits; such as kernel length, width, area, weight, unfilled spikelet and 1000-kernel weight, were detected. Highly significant associated markers were anchored physically using barley genome sequencing to identify candidate genes to either contain the SNPs or the closest gene to the SNP position. The results showed that 12 MTAs were specific for lateral spikelet traits, nine MTAs were specific for central spikelet traits and seven MTAs for both central and lateral traits. All together, the GWAS and candidate gene results support our hypothesis that lateral spikelet development could be regulated by loci different from those regulating central spikelet development.